Coping with Climate Extremes: Railways and Pastoralism During Australia's Federation Drought. (1st May 2022) - Brett, André; Ville, Simon
Transport networks can play an important role in responses to extreme climate events, especially when governments own the network and intervene directly. Railways occupied a central place in Australian rural development by the late nineteenth century, a topic that has been discussed widely by scholars of economic history. Much less is known about their contribution during the severe drought crises faced by rural communities. We investigate the role railways played during the Federation Drought of 1895-1903 in sustaining Australia's largest export industry, pastoralism. Government ownership of the railways enabled subsidies to be offered for the movement of livestock from drought areas and fodder to those areas. These policies assisted the rapid recovery of pastoral output and contributed to longer-term industry improvements. The intervention, however, came at significant financial cost to the railways, which was borne for the public good as part of an economic developmental purpose. The costs and benefits of drought relief policies continue to be debated today; our study demonstrates the major role transport networks can play in response to extreme climate events, both for immediate relief and in shaping subsequent behaviours.